1992
DOI: 10.1093/clind/15.3.453
|View full text |Cite
|
Sign up to set email alerts
|

Infections Due to Nocardia transvalensis: Clinical Spectrum and Antimicrobial Therapy

Abstract: Nocardia transvalensis, a rare Nocardia species, has previously been recognized as a cause of actinomycotic mycetoma. In a retrospective review of N. transvalensis isolates referred to the Centers for Disease Control (Atlanta) during the period January 1981 through January 1990, we identified 15 patient isolates. Four N. transvalensis isolates originated from one Australian reference laboratory; one patient's isolate that was identified by the Australian laboratory but that was not received at the Centers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 16 publications
1
47
0
1
Order By: Relevance
“…asteroides is the most common cause of primary pulmonary nocardiosis: this species has been estimated to cause at least 80% of cases (43). Rarely, other species, in particular, N. brasiliensis (551), have also been implicated in causing pulmonary disease in both immunocompromised and nonimmunocompromised patients (101,382).…”
Section: Epidemiologic Aspects Of Infection In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…asteroides is the most common cause of primary pulmonary nocardiosis: this species has been estimated to cause at least 80% of cases (43). Rarely, other species, in particular, N. brasiliensis (551), have also been implicated in causing pulmonary disease in both immunocompromised and nonimmunocompromised patients (101,382).…”
Section: Epidemiologic Aspects Of Infection In Humansmentioning
confidence: 99%
“…identified as causing invasive pulmonary and cutaneous infections. Patients with disseminated and potentially fatal N. brasiliensis (551), N. otitidiscaviarum (75,101), N. transvalensis (29,382,384), N.…”
Section: Epidemiologic Aspects Of Infection In Humansmentioning
confidence: 99%
“…N. transvalensis has since been found to be an uncommon but significant pathogen capable of causing disseminated infections, particularly in immunocompromised patients. In 1992, McNeil et al reported on the recovery of N. transvalensis from 16 patients from Australia, Canada, Nigeria, Spain, and the United States, 10 of whom had clinical and/or histopathologic evidence of infection (16). Of these patients with proven pulmonary or disseminated infection, six had definable underlying immunosuppressive conditions.…”
mentioning
confidence: 99%
“…Diseases that are caused by N. transvalensis include mycetomas, localized ocular infections, and primary pulmonary infection. N. transvalensis is now understood to cause life-threatening, invasive, and disseminated infections in severely immunocompromised patients [6] . Primary cutaneous disease usually occurs in immunocompetent hosts unlike other forms of nocardiosis.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-based methodologies have been shown to offer clear-cut advantages over traditional methods for the isolation of N. transvalensis complex that are difficult to recognize by conventional methods and present potential chemotherapeutic complications arising from their inherent resistance to aminoglycosides and amikacin in particular [6,[21][22][23] . Patients will benefit from optimal drug selection, particularly when primary drug resistance is noted and an alternative drug therapy is needed [24] .…”
Section: Discussionmentioning
confidence: 99%